The Effect of Excessive Ginger Intake on the Health of Mice and Liver Tissue - Khloud Adnan AL-Lehaibe; Tamara Amer Taha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Spices are one of the main ingredients frequently used in Arab and Asian kitchens. Therefore, we must research their harms in the service of society. Objective: This study aimed to investigate the effect of excessive ginger consumption on the phenotypic and histological structure of the mice liver. It is important to have a clear view of the spices that play a major role in damaging organs. Methodology: About 20 mice were used. I was orally (1g) to ginger for 50 days. that anesthetization, separating the liver, fixing by formalin, using the routine method to preparation block and sectioning (5um) then coloured with H&E. Results: Symptoms was the loss of weight, high temperatures, as well as the Gangrene at ends of the Ear, Tail. the liver appearance of severe congestion with a dark red colour, accompanied by bleeding and the appearance of fluid-filled swelling in the liver, forming what is called the liver abscess. Microscopy indicated a loss of the normal structure of the liver tissue. The sections also showed the emergence of the stages of programmed death of cells.Conclusion: We concluded that consuming spices in large quantities will lead to toxic liver toxicity, but it is not dangerous.